Express quantitative spectrophotometric determination of 2-(((3-(2-fluorophenyl)- 5-thio-4H-1,2,4-triazol-4-yl)imino)methyl)phenol as an active substance of a medicinal product for the treatment of mycoses - K. P. Miedviedieva; R. L. Prytula; O. P. Shmatenko; I. V. Bushuieva; V. V. Parchenko; L. I. Kucherenko; S. O. Vasiuk (Zaporožskij Medicinskij Žurnal)
Foot fungus (Candida, molds, dermatophytes) is a fairly common problem. According to the WHO, one-fifth of the world’s population is affected by fungal skin diseases. The prevalence of mycosis of the feet, which affects every second person, is especially increasing. Such a pathology can appear quite unexpectedly and at an inappropriate time. Today, Ukraine is under aggressive pressure from its northern neighbor, and military personnel are not only constantly at risk of receiving combat injuries and wounds, but also due to active hostilities, they may not have access to the necessary hygiene products, get cold, overheat in the sun, or not have time to change their clothes in time. and shoes. The reality is the absence or delay of treatment; the disease progresses and can spread quickly. If mycosis has appeared in one soldier, it can quickly affect others. Therefore, the problem of providing medical and pharmaceutical care is an urgent issue today. Expanding the assortment of drugs with the above action will ensure the needs of the Armed Forces and civilian patients with this dermatological pathology. It will be able to optimize antifungal therapy regimens. For quite a long time, 1,2,4-triazole derivatives have been a promising class of organic compounds that attract the attention of scientists from various fields. It has been proven that 2-(((3-(2-fluorophenyl)-5-thio-4H-1,2,4-triazole-4-yl)imino)methyl)phenol has high antifungal activity. A potential medicinal product based on this medicinal substance can be used for the treatment of various dermatological diseases. To continue the creation of new effective dosage forms for the effective therapy of mycosis of the feet, the urgent task of today is the development of an express, accurate, reliable, and affordable method of quantitative determination of the substance under study.